Low Temperature Synthesis of MnO2/Graphene Nanocomposites for Supercapacitors - Hao Huang; Guangren Sun; Jie Hu; Tifeng Jiao (Journal of Chemistry)
MnO2/graphene nanocomposites were synthesized through a simple route in a water-reflux condenser system. The as-prepared composites were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, Raman microscope, and Brunauer-Emmett-Teller surface area analysis. Capacitive properties of the synthesized composite electrodes were investigated via cyclic voltammetry, galvanostatic charge/discharge, and electrochemical impedance spectrometry in a 0.5 M Na2SO4 electrolyte. Results show that this method can control the morphology and structure of MnO2 loaded onto the graphene sheets. Because excessive MnO2 enwrapping graphene would affect the overall conductivity, the composite prepared by lower temperature has better characteristics of supercapacitor. 60-MnO2/graphene composite (48 wt% MnO2) displays the specific capacitance as high as 350 F/g at 1000 mA/g, which is higher than that of 100-MnO2/graphene (302 F/g), and it is almost two times higher than that of MnO2 (163 F/g). Furthermore, the composite exhibits excellent long cycle life along with ~93% specific capacitance retained after 5000 cycle tests.